Moralsk stress som daginstitutionelt fænomen – en begyndende indkredsning - Plum, Maja; Pallesen, Eva; Schmidt, Lene S.K.; Gylling, Martin (Tidsskrift for Professionsstudier, 2025)
Studies in elderly care, policing, hospitals, and schools point to moral stress as (part of) the explanation for the current recruitment and retention crisis in the welfare professions. Moral stress refers to the strain that arises when the working conditions hinder living out what one professionally assesses is the right thing to do. Experiences of failure and powerlessness are thus involved. Based on an ongoing study, this article seeks to understand moral stress as a phenomenon in a daycare context. We argue that moral stress as a daycare phenomenon must consider the working conditions as more than just a framework, but something that interweaves with and into the professionals’ experiences and feelings of being professional. Taking an entrance through the sociology of emotions, we show how different moral imperatives and emotional demands pull pedagogues and pedagogical leaders in contradictory directions and stretch them into different ambivalences.